Investigation of ultrasonic welding of carbon fiber reinforced thermoplastic to an aluminum alloy using a interfacial coating. Issue 11 (18th August 2021) - Kalyan Kumar, R.; Omkumar, M.
ABSTRACT: An investigation on joining of carbon fiber-reinforced thermoplastics to an aluminum alloy 6061 has been demonstrated using ultrasonic plastic welding process. A separate energy director, as required for focusing heat generation at interface during ultrasonic plastic welding, is replaced by high-performance thermoplastic coating on aluminum via a fluidized bed to make the process convenient for industrialization. Besides this, the functional coating acts as an insulator that resists galvanic corrosion and avoids fretting damage on metallic substrates. Critical welding parameters were experimentally realized (weld time: 900 ms, hold time: 1200 ms, and horn pressure: 0.5 MPa) for a maximum shear failure load in a lap-type joint configuration that showed uniform melting with higher fusion between thermoplastics. The fracture surface and cross-section morphology were examined for different joint nomenclatures. Delamination and first-layer ply failures associated with interlaminar shear of composites were predominant with an effective interfacial adhesion (mechanical anchoring) on aluminum asperities yielding a structurally rigid joints. A significant strength improvement of 40% was attained in mechanically treated aluminum substrates. An appreciable joint strength in comparison with adhesive bonding was obtained within a cycle time of 2.1 s. The real-time transient temperature analysis during welding provided a strong correlation with the weld formation.